The Effect of Corporate Action / Stock Split Corporate Action on LQ-45 Stock Performance - Ahmad Rezkhy Ramadhan; Failur Rahman (Manunggal Halim Jaya, 2024)
All companies listed on the Indonesia Stock Exchange always expand, pay debts, or increase capital in the form of corporate actions. Also included in the LQ-45 registered companies also carried out corporate actions. Therefore, this study aims to analyze the influence of stock split corporate actions on LQ-45 stock performance. This study uses a quantitative research method using descriptive analysis techniques. Hypothesis testing in this study uses an analysis tool, namely Eviews. Based on the results of the study, it shows that there is an influence of corporate action/corporate action stock split on the performance of LQ-45 shares. With the corporate action of stock split, the company is expected to add investors and increase stock purchase transactions at affordable prices.